Arsip Surat Keluar Masuk Surat BKPSDM Kabupaten Nabire Berbasis Web - Kristia Yuliawan; Diana Wonda (Jurnal Teknologi dan Informatika, 2025)
The management of incoming and outgoing correspondence in an effective and efficient manner is a crucial aspect in supporting the performance of government organizations, including the Civil Service and Human Resource Development Agency (BKPSDM) of Nabire Regency. As an institution responsible for handling personnel administration, BKPSDM regularly receives and sends a large volume of official letters every month. However, the archiving process is still conducted manually using physical media such as folders, filing cabinets, and record books. This manual system presents several drawbacks, including the risk of data loss, delays in document retrieval, recording errors, and the potential for physical damage to archives due to environmental factors. This study aims to design and develop a digital archiving system for incoming and outgoing letters using the Waterfall software development methodology. The Waterfall method is selected because of its structured approach and suitability for projects with clearly defined requirements. The stages in this method include requirements analysis, system design, implementation, testing, and maintenance. The result of this research is a web-based letter archiving information system that can efficiently record, store, and retrieve correspondence accurately and securely. The implementation of this system is expected to improve the efficiency and accountability of letter archive management at BKPSDM Nabire Regency and support the acceleration of digitalization in government administrative services.